Corporate Responsibility in Recognizing the Value of Human Asset - Jeremy Cripps (An Overview on Business, Management and Economics Research Vol. 5, 2023)
This chapter provides research on the top 50 of the Fortune 500 companies to research potential for material deficiency. Such a material and significant deficiency in the reporting of corporate assets might identify a real need to provide financial statement stakeholders with a “fair” knowledge of the value of corporate human capital. Corporate social responsibility is a business model by which companies make a concerted effort to operate in ways that enhance rather than degrade society and the environment. The machinery, equipment, inventory, and other assets of a twenty-first-century corporation have no actual economic value unless they are used. Corporations continue to disregard human value, despite the accounting profession’s advice. Nonetheless, there is a growing recognition that people account for the majority of business productive capacity when compared to the current and fixed assets reflected in company financial accounts. There is a need to provide stakeholders with a “fair” knowledge of the value of corporate human capital to provide a higher standard of transparency and accountability in international financial reporting and to provide the basis for research into the sustainability and potential expansion of growth in the world economy. The knowledge foundation for wise and efficient investments in human capital will come from a suitable standard for human capital valuation. Investments that are both profitable and efficient will be especially beneficial to governments, the service sector, and individuals looking to advance European development. In fact, the legitimacy of financial statements that omit "the most valuable" business assets is being questioned by the Organization for Economic Cooperation and Development (OECD). Recently, the OECD has noted that human capital may be measurable “by the output potential of specific competencies”; “the fruits of (corporate) investment”; the objective measurement of the market “rental” price of human capital; and lastly, perhaps self-evident when it comes to physical capital, the output potential of corporate investment in their human capital inventory. The extraordinary failure of financial experts to focus on analyzing their human capital needs is perhaps not surprising, when the focus on production has proved to be so successful. Indeed, the very success of the intellect which has generated productivity is the very strongest evidence that a similar focus on human capital is likely to bring even more business success and prosperity.